Is Fabry disease an indication for a transcatheter aortic valve implantation? A case of successful surgical aortic valve replacement with an adverse postoperative course: Je Fabryjeva bolezen indikacija za transkatetrsko vstavitev aortne zaklopke? Prikaz primera uspešne kirurške zamenjave aortne zaklopke z neugodnim pooperativnim potekom - Antonič, Miha (Acta Medico-Biotechnica, 2021)
Purpose: Fabry disease (FD) is an extremely rare X-linked lysosomal storage disorder caused by a deficiency of the enzyme α-galactosidase A, which results in intracellular accumulation of glycosphingolipids. In the heart, accumulating sphingolipids and accompanying fibrosis promote hypertrophy, conduction disturbances, thickening of the valves, and accelerated coronary artery disease resulting in substantial morbidity and mortality.Case report: Here, we present a case of a 57-year old male with FD, severe aortic valve stenosis, and permanent atrial fibrillation who underwent successful and uncomplicated surgical aortic valve replacement, but postoperatively developed severe complications of nearly all organ systems, which resulted in death.Conclusion: Although the patient risk profile did not meet the criteria for transcatheter aortic valve implantation, this treatment option is presented and discussed as a possible or even preferable alternative to surgery.
Keywords: Fabry Disease; aortic valve stenosis; aortic valve replacement; multiple organ failure